Transformative Civic Education in Democratic Societies - Hoggan-Kloubert, Tetyana (Transformations in Higher Education Series., 2023)
"In this collection, scholars from around the world report and reflect on civic adult education, examining approaches, paradigms, and concepts that help us to act in culturally, ethnically, linguistically, and religiously diverse societies. This book offers examples of the roles that civic education has played and can play in different societies, making democracies stronger and more peaceful"--